Recommending Best Practices for Accelerating Hybrid Cloud Adoption - Mone, Manoj Ravindra (Digital Repository of Theses - SSBM Geneva, 2025)
The aim of this research is to study hybrid cloud adoption and find the various factors that affect this adoption. This study aims to understand the challenges that bog down the teams embarking on the Hybrid Cloud adoption journey and aims to find various steps that can be taken to accelerate the adoption of hybrid cloud. Through this thesis we intend to investigate the key factors affecting the adoption of hybrid cloud. Given the plethora of applications that a typical organization implements, we wish to study if there are any specific type of applications that are a better choice for deployment on hybrid cloud. This thesis aims to find what are the various approaches, tools and strategies that can help the acceleration of hybrid cloud adoption by the enterprises. We aim to do this by extensive literature review, face-to-face and Zoom interviews and survey questionnaire.